LH-21, A Peripheral Cannabinoid Receptor 1 Antagonist, Exerts Favorable Metabolic Modulation Including Antihypertensive Effect in KKAy Mice by Regulating Inflammatory Cytokines and Adipokines on Adipose Tissue - Dong, Ziqi; Gong, Hui; Chen, Yadan; Wu, Hong; Wu, Jun; Deng, Yinghong; Song, Xinmao (Frontiers in Endocrinology, 2018)
Patients with obesity are susceptible to hypertension and diabetes. Over-activation of cannabinoid receptor 1 (CB1R) in adipose tissue is proposed in the pathophysiology of metabolic disorders, which led to the metabolic dysfunction of adipose tissue and deregulated production and secretion of adipokines. In the current study, we determined the impact of LH-21, a representative peripheral CB1R antagonist, on the obesity-accompanied hypertension and explored the modulatory action of LH-21 on the adipose tissue in genetically obese and diabetic KKAy mice. 3-week LH-21 treatment significantly decreased blood pressure with a concomitant reduction in body weight, white adipose tissue (WAT) mass, and a slight loss on food intake in KKAy mice. Meanwhile, glucose handling and dyslipidemia were also markedly ameliorated after treatment. Gene expression of pro-inflammatory cytokines in WAT and the aortae were both attenuated apparently by LH-21, as well the mRNA expression of adipokines (lipocalin-2, leptin) in WAT. Concomitant amelioration on the accumulation of lipocalin-2 was observed in both WAT and aortae. In corresponding with this, serum inflammatory related cytokines (tumor necrosis factor α, IL-6, and CXCL1), and lipocalin-2 and leptin were lowered notably. Thus according to current results, it can be concluded that the peripheral CB1R antagonist LH-21 is effective in managing the obesity-accompanied hypertension in KKAy mice. These metabolic benefits are closely associated with the regulation on the production and secretion of inflammatory cytokines and adipokines in the WAT, particularly alleviated circulating lipocalin-2 and its accumulation in aortae.